Transient Simulation of the Six-Inlet, Two-Stage Radial Turbine under Pulse-Flow Conditions - Dariusz Kozak; Paweł Mazuro (Energies, 2021)
In recent years, the automotive sector has been focused on emission reductions using hybrid and electric vehicles. This was mainly caused by political trends promoting “green energy”. However, that does not mean that internal combustion engines (ICEs) should be forgotten. The ICE has still the potential of recovering energy from exhaust gases. One of the promising ways to recover energy is turbocharging. Over the years engine manufacturers have designed very efficient turbocharger systems which have greatly increased the overall engine efficiency. This led to pollutant emission reductions. This paper presents the results of the three-dimensional (3-D) numerical simulations of the two-stage, six-inlet turbocharging system under the influence of unsteady, pulsed-flow conditions. The calculations were carried out for three turbine speeds. The most interesting results of this study were the separation of exhaust gases coming from the six-exhaust pipes and the performance of both stages under pulse-flow conditions. The two-stage turbocharging system was compared against the single-stage turbocharging system and the results showed that the newly designed two-stage turbine system properly separated the exhaust gases of the adjacent exhaust pipes.